Kreativität im Schnittpunkt der Observanzen/ Creatività e osservanza : Italienische Literatur um 1600 zwischen Gegenreformation und Regelpoetik/ Letteratura italiana del Seicento tra Controriforma e normatività poetica - Bosi, Carlo; Carminati, Clizia; Fantappiè, Irene; Fingerle, Maddalena; Föcking, Marc; Huss, Bernhard; Mehltretter, Florian; Nelting, David; Paltrinieri, Ilaria; Wiener, Claudia (2023)
Italian literature emerged around 1600 at the intersection of poetological and religious attempts at standardization and under the attentive watch of a literary community and its critical discussions as well as the censorship and inquisition of the Counter-Reformation. This volume sheds light on creativity under the conditions of this twofold "observance" by looking at texts from various genres written between ca. 1550 and 1650.